NBM (Encyclopedia of Clinical Neuropsychology, 2011)
Hyperpolarized MRI is a medical imaging technology that has been used so far only in focused clinical studies. This technology enables metabolic imaging without ionizing radiation and is combined with standard-of-care MRI protocols. Unlike metabolic imaging performed with radiolabeled materials (e.g., PET and SPECT), hyperpolarized MRI enables differentiation between the injected metabolic substrate and its product(s). In this way, the number of imaging contrasts that may be attained is relatively large. The purpose of this review is two-fold: to provide coherent terminology for the various contrasts obtained in HP-MRI to facilitate further development in medicine and to highlight its potential contribution to liver nodule characterization. We reviewed 33 hyperpolarized MRI papers published from 2013 to 2024 that describe clinical studies in human subjects and patients, and characterized the metabolic contrast provided by this technology across various organs and in cancer tumors. We have further reviewed 20 preclinical studies of hyperpolarized MRI in the liver to evaluate the potential of this technology for early detection and characterization of hepatocellular carcinoma. Most clinical studies have used a single hyperpolarized substrate, namely, pyruvate, labeled with carbon-13 at position 1 ([1- 13 C]pyruvate). Even with this single substrate, the number of possible imaging contrasts is high, making the interpretation of these images challenging. We aimed to explain these imaging contrasts and provide a consistent nomenclature for them that will serve the medical community. Preclinical MRI studies using hyperpolarized substrates suggest the potential to characterize liver nodules in patients. In summary, hyperpolarized MRI is a promising clinical imaging modality in oncology; however, the small number of patients investigated so far precludes addressing possible biological confounding factors. Further studies are required for improving tumor characterization using this technology, and studies in liver imaging aimed at early detection of HCC are warranted.